Desenvolvimento do programa de computador gapblaster: uma ferramenta gráfica para fechamento de gaps em genomas procariotos - MIRANDA, Fábio Malcher (2020)
Among the main challenges that prevent scientists from reaping the benefits of genome assembly are the high experimental costs, which make it difficult to finish assemblies. Although there are various computational solutions that assist in the finishing phase, these tools are basically "black boxes" that do not present enough information about the changes being made in the genome and often fail to fill in all the gaps left by the assemblers. In this work, these issues are addressed through the creation of the software GapBlaster, a graphical tool that aims to reduce the fragmentation of genomes assembly and speed-up finishing the latter. The proposed algorithm uses as input a FASTA file containing the scaffolds of the genome and one or more FASTA files containing the contigs, which may come from different assemblers or even from other sequencing experiments. The contigs are then aligned against the scaffolds through the software Legacy BLAST, BLAST + or MUMmer and the identified alignments belonging to the same contig that can also close gaps are then displayed to the user for inspection through the graphical user interface. GapBlaster’s performance was evaluated on NGS data obtained from the assemblies of the bacterias Staphylococcus aureus and Rhodobacter sphaeroides, both acquired from the GAGE project. Additionally, NGS data from the genome assembly of Corynebacterium pseudotuberculosis was used. Compared with similar tools, the results of GapBlaster are satisfactory and it has the advantage of offering a graphical user interface for inspection of closed gaps. GapBlaster was developed in Java and is available for download at <https://sourceforge.net/projects/gapblaster/>. GapBlaster requires the installation of JDK 8 and Legacy BLAST, BLAST + or MUMmer.